Classification of ξs-quadratic stochastic operators in 2D-simplex - Mukhamedov, Farrukh; Mohd Jamal, Afifah Hanum (Universiti Teknologi MARA, Pulau Pinang, MALAYSIA, 2010)
In this paper we introduce a new class of quadratic stochastic operators called sξ-QSO. We classify such operators on 2D-simplex, into six non-isomorphic classes, with respect to their conjugacy and renumeration of the coordinates.